The Portuguese Guidelines and Patients Values - Santos, Paulo (2015)
Introduction: Clinical guidelines are support tools, aiming to improve quality of the clinical practice. Patient centered care allows best satisfaction rates, with greater health self-management, and potential gains in quality with fewer costs.Objective: To evaluate the integration of patients’ values in Portuguese guidelines.Material and Methods: We reviewed the 18 guidelines about cardiovascular diseases published in Portugal from 2011 to 2013, searching for the integration of patients’ ideas, fears, expectations and preferences.Results: Eight guidelines were related to diagnosis approach and 10 with treatment. We found references to patients’ values in 5 (28%) guidelines, all about treatment aspects. The incorporation of patients’ expectations was the most present feature. Reference to financial costs was present in 78% of the guidelines.Discussion: Clinical guidelines are health technology instruments available to practitioners in order to improve the quality of care provided to patients, who are the real users of these tools. As in other countries, there is a tendency to disregard the users’ value systems in the conception of the guidelines, giving the privilege to a population logic, not always applicable to the individual, and to financial arithmetic with low support in cost-effectiveness assessments. In the Portuguese case, the way guidelines were proposed conditioned also some suspicion both in the professionals and in the users.Conclusion: Portuguese guidelines have low incorporation of references to patients’ values. This is more evident when questions about diagnosis are addressed, placing patients in a secondary role in the clinical decision-making process with potential losses in quality of care and eventual increase in costs.